Optimal charging control of electric vehicles in smart grids - Tang, Wanrong; Zhang, Ying Jun (Springer, 2017)
"This book introduces the optimal online charging control of electric vehicles (EVs) and battery energy storage systems (BESSs) in smart grids. The ultimate goal is to minimize the total energy cost as well as reduce the fluctuation of the total power flow caused by the integration of the EVs and renewable energy generators. Using both theoretic analysis and data-driven numerical results, the authors reveal the effectiveness and efficiency of the proposed control techniques. A major benefit of these control techniques is their practicality, since they do not rely on any non-causal knowledge of future information. Researchers, operators of power grids, and EV users will find this to be an exceptional resource. It is also suitable for advanced-level students of computer science interested in networks, electric vehicles, and energy systems"--Provided by publisher.
Keywords: Electric vehicles -- Batteries.; Battery charging stations (Electric vehicles); Smart power grids.; elektronické knihy; electronic books